The Effects of a Low Cost Hydro Cooling System on the Postharvest Quality Characteristics of Selected Tropical Fruits and Vegetables - Chepngeno, Joyce; Kinyuru, John; Nenguwo, Ngoni; Owino, Willis (Journal of Postharvest Technology, 2015)
Quality of fresh produce getting to consumers is influenced by the postharvest  handling practices. In developing countries, low cost hydrocooling system  offers affordable means to curb postharvest loses of perishables. This study  was undertaken to establish the effect of combining hydrocooling and low  temperature storage on postharvest quality of perishables, specifically carrots,  courgettes, tomatoes and African eggplants. Mature good quality produce were  harvested and divided into four portions. Two portions were hydrocooled using  chilled water (2±10C) and change in temperature monitored. The other two  were controls. Hydrocooled and control samples were stored at 100C and 20- 250C at 95%relative humidity. Respiration rates, weight loss, soluble solids  and titratable acidity changes were assessed at 2 days interval for 9 days. The  percentage weight loss on day 9 was 1.83 %, 13.91 %, 8.09 %, 6.25 % and  titratable acidity was 0.24%, 0.019%, 0.13%, in samples hydrocooled and  stored at 10 0compared to 4.30%, 28.35%, 20.03%, 2.15%weight loss and  0.32%, 0.037%, 0.16%,titratable acidity in control for tomatoes, courgettes  carrots and African eggplants, respectively. Respiration rates and soluble  solids were higher in controls. Storage time had a significant effect (P≤0.05)  on produce quality.
Keywords: Cooling time; Hydrocooling; Low temperature storage Postharvest Quality